Operation Approach of Happy Workplace Model in Eastern Part of Thailand - ซึ้งจิตสิริโรจน์, วุฒิเดช; แสดงหาญ, พรรัตน์ (KKBS Journal of Business Administration and Accountancy, 2019)
The objective of this research was to study the operation approach of happy workplace model in eastern part which consisted of the happy-8 model that influences the building of happy workplace, obstacles, problems, and solution. This is qualitative research and a case study. The sample group included the representatives of 5 happy workplaces. The result came from the interview of the informants who shared a similar idea relating to the operation approach of happy workplace model in eastern part. In consequence, the factors that affect the happy workplace include executive’s policy and demands of having happy employees which are the beginning of the happy activities due to happy-8 model that is composed of 1. Happy Body: to encourage exercising 2. Happy Heart: visiting employees 3. Happy Relax: arranging the annual traveling trip 4. Happy Brain: founding the training center and library. 5 Happy Soul: having morality and arranging moral activity project 6. Happy Money: knowing how to spend money and obtaining knowledge about finance 7. Happy Family: arranging the traveling trip for employees and their families. 8. Happy Society: providing social aiding services. For the activity, obstacles/problems are found, which are the employees lack the knowledge of the true happy workplace, the organization is unable to operate some activities, the employees have no desire to join some activities, the organization deprives of the leadership employees, arranging excessively frequent activities, and the executives see the effect towards the production process due to the reduction of working hours for operating the activities. For the solutions, the organization should study the other’s operation to apply knowledge, surveying the employees’ demands, explaining the operation approach and result to the managing team, and collaborating in making plans with the production department.